Penggunaan Teknologi dalam Rangka Mengembangkan Usaha Kuliner di Tiban Centre - Carin, Latycia; Selvina, Selvina; Pratama, Nico; Melissa, Vina; Hendri, Hendri; Christoffer, Christoffer (National Conference for Community Service Project (NaCosPro), 2019)
The Objective of this activities are : (a) to train students to mingle with the society; (b) to show the importance of giving service to our society; (c) to introduce digital marketing to micro, small & medium enterprises (MSME) in order to increase market competitiveness. The research is conducted in Tiban Centre by interviewing 4 random foods & beverages business owners. The result shows that 3 out of 4 business owners are interested in digital marketing but due to low technology literacy, they don?t know how to conduct it. The digital marketing we are using is called Go-Food, which is one of the largest single-market food delivery app in Indonesia. By using this e-commerce feature, we believe that their business will grow faster and bigger in no time.